On predicting 300-mb contour heights and temperatures from 500-mb data - GUPTA, M. G. (MAUSAM, 1963)
It has been shown in this paper that simple relationships exist, in India between 1000-500 mb and 500-300 mb thicknesses and also between 500-300 mb thickness and 300 mb temperature. The utility of these relationships in providing a quick and fairly accurate check during analysis is brought out. The possibility of using these relationships for 300 mb prognosis has also been indicated.